Plasma polymer gradients : developing a tool for the screening of biological responses to surfaces - Zelzer, Mischa (2009)
Controlling the interaction of cells with a material surface is of major interest in the field of biomedical material science. Plasma polymers are an attractive way to modify the surface chemistry of a material because this technique is versatile and can be applied to a wide range of different surfaces. The aim of the present work is to prepare a new chemical gradient tool using plasma polymerisation and assess its ability to provoke position dependent cell-surface interactions. A novel diffusion based approach is used to develop gradients from hydrophobic hexane (ppHex) to more hydrophilic allylamine (ppAAm) plasma polymers. The surface of the gradient and that of uniform control samples is characterised using WCA, XPS, ToF-SIMS and AFM. This data shows that the most distinct gradient was found in the wettability profile which can be controlled by changing the size of the opening through which diffusion of depositing species from the plasma occurs. The mechanism of the gradient formation is studied with channels of well defined cross sections. The deposition rate obtained on these samples shows a sharp drop off in the amount of ppHex deposited from the plasma starting 2 mm in advance of the opening. An estimation of the sheath dimensions indicates that this corresponds to the sheath thickness. It is suggested that plasma deposition through small openings such as pores depends on the relative dimensions of the sheath and the pore cross section. Inside the channels, oligomer formation is observed in the gas phase, presumably following a nucleophilic addition reaction mechanism. To study the stability of these plasma polymer surfaces in physiological conditions, surface analysis is also carried out on samples exposed to aqueous solutions. Some changes in the topography of the plasma polymer films are found. Most notably, uniform samples of ppHex deposited on top of ppAAm show the formation of blisters that are not observed on other samples. It is argued that these blisters are the result of water penetrating through the top ppHex layer and interacting with the more hydrophilic ppAAm or glass substrate. 3T3 fibroblasts cultured on the gradients show a gradual increase in cell density. This cell density gradient can be related linearly to the wettability gradient on the surface with non-linear relationships being observed with other surface parameters such as the ppHex thickness. The cell number on uniform ppAAm is much greater than on the ppAAm side of the gradient. Data from experiments with non-proliferating 3T3 fibroblasts indicates that the differences between the gradient and uniform ppAAm as well as the cell density increase along the gradient have their origin in a different number of cells adhered to the surface within the first 24 hours of cell culture. The adsorption of albumin and fibronectin on the plasma polymers demonstrate that displacement of the former by the latter takes place on the surface when adsorbed competitively. However, this displacement does not occur in different extents along the gradient surface, suggesting that protein displacement can not explain the increase in cell density towards the ppAAm end of the gradient.